Population Structure of Non-ST6 Listeria monocytogenes Isolated in the Red Meat and Poultry Value Chain in South Africa - Matle, Itumeleng (Microorganisms, 2020)
Meat products have been implicated in many listeriosis outbreaks globally, however there is a dearth of information on the diversity of L. monocytogenes isolates circulating in food products in South Africa. The aim of this study was to investigate the population structure of L. monocytogenes isolated in the meat value chain within the South African market. Based on whole-genome sequence analysis, a total of 217 isolates were classified into two main lineage groupings namely lineages I (n = 97; 44.7%) and II (n = 120; 55.3%). The lineage groups were further differentiated into IIa (n = 95, 43.8%), IVb (n = 69, 31.8%), IIb (n = 28, 12.9%), and IIc (n = 25, 11.5%) sero-groups. The most abundant sequence types (STs) were ST204 (n = 32, 14.7%), ST2 (n = 30, 13.8%), ST1 (n = 25, 11.5%), ST9 (n = 24, 11.1%), and ST321 (n = 21, 9.7%). In addition, 14 clonal complex (CCs) were identified with over-representation of CC1, CC3, and CC121 in “Processed Meat-Beef”, “RTE-Poultry”, and “Raw-Lamb” meat categories, respectively. Listeria pathogenic islands were present in 7.4% (LIPI-1), 21.7% (LIPI-3), and 1.8% (LIPI-4) of the isolates. Mutation leading to premature stop codons was detected in inlA virulence genes across isolates identified as ST121 and ST321. The findings of this study demonstrated a high-level of genomic diversity among L. monocytogenes isolates recovered across the meat value chain control points in South Africa.